Shape Memory Alloy Capsule Micropump for Drug Delivery Applications - Kotb, Youssef Mohamed (AUC Knowledge Fountain, 2024)
Implantable drug delivery devices have many benefits over traditional drug administration techniques and have attracted a lot of attention in recent years. By delivering the medication directly to the tissue, they enable the use of larger localized concentrations, enhancing the efficacy of the treatment. Passive-release drug delivery systems, one of the various ways to provide medication, are great inventions. However, they cannot dispense the medication on demand since they are nonprogrammable. Therefore, active actuators are more advantageous in delivery applications. Smart material actuators, however, have greatly increased in popularity for manufacturing wearable and implantable micropumps due to their high energy density. This proposal introduces a novel design for a resistively actuated shape memory alloy (SMA) capsule micropump with enhanced power density. The primary objective of this proposal is to optimize this micropump for efficient drug delivery applications. The novel design being proposed involves the integration of a drug reservoir that is replaceable and built-in within the pump package. This integration results in the creation of a self-contained preloaded capsule pump, which has an overall pump volume measuring 424.7 uL. The novel design yields a micropump that is characterized by its compactness, simplicity, and affordability. Additionally, this design significantly minimizes the likelihood of contamination, as evidenced by the nearly negligible dead volume values achieved. The pump is composed of SMA (Shape Memory Alloy) wires made of NiTi-alloy (SMA), which are arranged in a coiled configuration and enclosed within a flexible polymeric casing. The actuation of the pump is achieved through the application of joule heating. In contrast to the diaphragm and peristaltic shape memory alloy (SMA) micropump designs that operate in a transverse manner, our design operates longitudinally, following the direction of the greatest mechanical compliance. This longitudinal actuation allows for significant strokes, reaching approximately 5.6 mm at a deflection ratio of 27%. Additionally, this design enables actuation speeds of up to 11 mm/s and static head pressures of up to 14 kPa (105 mmHg) with an input power of 7.1W. Consequently, this design facilitates high throughputs, surpassing 2524 uL/min under conditions of the free convention. A mathematical model was formulated with the objective of optimizing the geometrical parameters of the pump as well as the material used for its enclosure. According to the model's findings, the utilization of enclosure material with low stiffness in conjunction with a thinner diameter of SMA wire would yield the highest deflection while operating at the lowest power rating. To prove its viability for drug delivery applications, the pump was tested for 2 applications. The first one is an Internet-of-Things (IoT) based, wirelessly reconfigurable, sufficiently miniaturized micro-pumping device more suitable for personalized cancer therapy. The final product is intended to be locally implanted in tumor tissue, with the anticancer drug stored in refillable reservoirs. The wireless system facilitates the analysis of the transmitted data instantly, thus enabling control and reconfiguration of the drug administration regimen. The system was successfully implemented, tested in vitro, and proven to deliver a model anticancer drug accurately and achieve a cytotoxic effect on breast cancer cells (>71%) with an optimized remotely controlled bolus dosing regimen. The proposed pumping solution is intended to improve the therapeutic performance of cancer drugs by reversing their resistance. Moreover, the second one proposes an IoT-enabled miniaturized remote auto-injector supported by smartwatch health monitoring for the emergency medical treatment of allergy- induced anaphylaxis patients. A smartwatch monitors the patient's vital biomarker data (heart rate, oxygen saturation, and fall detection), which are sent in real-time to a local server or cloud. Upon identification of the risk of anaphylaxis, the auto-injector device worn by the patient is actuated wirelessly to instantly inject an epinephrine emergency dose to save the patient's life by restoring cardiac rhythm and controlling mucosal congestion, glaucoma, and asthma. In the meantime, a physician or care provider can monitor the patient's status in real-time. The auto- injector consists of two shape memory alloy (SMA) actuators injecting and retracting a subcutaneous injection needle and connected to an in-house developed micropump loaded with epinephrine. The system's response time is 3 seconds, whereas the needle penetration and drug injection are completed in 15 seconds. Epinephrine dosage can be injected at a maximum flow rate of 2524 μl/min against a maximum of 14 kPa backpressure. The system features a novel feature by retracting the needle immediately after the injection to avoid the patient's injury. Furthermore, the SMA actuation force and system package can be adapted for instant intramuscular injection; meanwhile, the needle retraction feature prevents skin and muscle injury.